2018
DOI: 10.1002/jid.3336
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Microcredit's Poverty‐Reducing Promise: Evidence from Cambodia

Abstract: This article analyses the effects of microcredit offered by microfinance institutions on household poverty in terms of household food consumption, with data from the Cambodia Socio‐Economic Survey conducted in 2014. The analysis is carried with an endogenous switching model accounting for endogenous selection bias resulting from unobservable confounders and for inherent differences between household borrowers and non‐borrowers in terms of food consumption functions. The results suggest that households, whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 44 publications
(112 reference statements)
0
12
0
Order By: Relevance
“…The topic of microfinance is generating a lively debate in the reference literature on its efficacy (Khavul, 2010;Bateman & Chang, 2012;Garikipati, 2017;Cull & Morduch, 2017;Seng, 2018), and many researchers acknowledge its importance and the value of social participation in poverty alleviation (Newman, et al, 2014;Banerjee et al, 2015a;Banerjee et al, 2015b;Chen et al, 2017). Previous reports have been unable to demonstrate that it is effective in helping people emerge from poverty, but there is a consensus that microfinance gives to the poor entrepreneurs a greater degree of freedom to make choices and obtain financial investments, since they do not have access to formal banks (Newman et al, 2014;Mersland & Strøm, 2010;Garikipati, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The topic of microfinance is generating a lively debate in the reference literature on its efficacy (Khavul, 2010;Bateman & Chang, 2012;Garikipati, 2017;Cull & Morduch, 2017;Seng, 2018), and many researchers acknowledge its importance and the value of social participation in poverty alleviation (Newman, et al, 2014;Banerjee et al, 2015a;Banerjee et al, 2015b;Chen et al, 2017). Previous reports have been unable to demonstrate that it is effective in helping people emerge from poverty, but there is a consensus that microfinance gives to the poor entrepreneurs a greater degree of freedom to make choices and obtain financial investments, since they do not have access to formal banks (Newman et al, 2014;Mersland & Strøm, 2010;Garikipati, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…This attitude can turn clients into defaulting borrowers because their having used the credit to cover other needs can lead to a situation where they are unable to raise capital to cover the loan (Chen et al, 2017). That is why Chen et al (2017) and Seng (2018) suggest that microfinance may not always generate positive results for borrowers. Bateman and Chang (2012) are much more severe in their criticism, claiming that microfinance is a weapon of neoliberalism, a "trap for the poor".…”
Section: Microfinance Programsmentioning
confidence: 99%
“…Over the past decade over‐indebtedness has grown considerably, and Cambodia has recently become a focal point for conversations about over‐indebtedness among microcredit borrowers (Bateman, 2017; Bylander, 2015; Liv, 2013; Rozas, 2016). In 2012 as many as a quarter of borrowers in saturated areas were experiencing over‐indebtedness (Liv, 2013), and since this time over‐indebtedness has become an even greater economic, social and political concern (Bylander et al., 2019; see also Seng, 2017, 2018). Over the past two years delinquency rates and non‐performing loans have increased across the sector, and industry experts suggest that the sector is over‐heated, and thus at risk of crisis.…”
Section: The Cambodian Casementioning
confidence: 99%
“…The second group of researchers asserts that rural financial development has no impact on poverty reduction, and even exacerbates income inequality (Hermes, 2014;Khandker & Koolwal, 2010;Seng, 2018;Seven & Coskun, 2016). For instance, Khandker and Koolwal (2010) found that although both formal and informal credits increased non-farm incomes, they did not decrease the number of extremely poor households overall.…”
Section: Introductionmentioning
confidence: 99%
“…Seven and Coskun (2016) reached similar conclusions. Seng (2018) argued that extremely poor households that acquired microcredit fared worse in food consumption. Hussain and Thapa (2012) argued that the negative effect of rural credit primarily owed to institutional constraintsfarmers with considerable landholdings and family assets are more likely than smallholders to obtain formal credit at lower transaction costs.…”
Section: Introductionmentioning
confidence: 99%